2020
DOI: 10.1084/jem.20191284
|View full text |Cite
|
Sign up to set email alerts
|

Continuous mitotic activity of primitive hematopoietic stem cells in adult mice

Abstract: The proliferative activity of aging hematopoietic stem cells (HSCs) is controversially discussed. Inducible fluorescent histone 2B fusion protein (H2B-FP) transgenic mice are important tools for tracking the mitotic history of murine HSCs in label dilution experiments. A recent study proposed that primitive HSCs symmetrically divide only four times to then enter permanent quiescence. We observed that background fluorescence due to leaky H2B-FP expression, occurring in all H2B-FP transgenes independent of label… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…Cell-cycle-dependent labeling studies reported that HSCs divide infrequently (between 2 and 7% of HSCs per day) and indicate that they are not a uniform population in this respect (Kiel et al, 2007;Wilson et al, 2008;Foudi et al, 2009;Oguro et al, 2013;Akinduro et al, 2018). The least proliferative ("proliferation-label retaining") HSCs have been termed dormant (Wilson et al, 2008;Bernitz et al, 2016;Cabezas-Wallscheid et al, 2017), but careful analysis of label dilution has shown that even these cells cycle at low rate (Morcos et al, 2020). Cell-cycle-dependent labeling approaches could not disentangle asymmetric and symmetric self-renewal of HSCs nor assess HSC differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-cycle-dependent labeling studies reported that HSCs divide infrequently (between 2 and 7% of HSCs per day) and indicate that they are not a uniform population in this respect (Kiel et al, 2007;Wilson et al, 2008;Foudi et al, 2009;Oguro et al, 2013;Akinduro et al, 2018). The least proliferative ("proliferation-label retaining") HSCs have been termed dormant (Wilson et al, 2008;Bernitz et al, 2016;Cabezas-Wallscheid et al, 2017), but careful analysis of label dilution has shown that even these cells cycle at low rate (Morcos et al, 2020). Cell-cycle-dependent labeling approaches could not disentangle asymmetric and symmetric self-renewal of HSCs nor assess HSC differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…This study implied that HSCs somehow keep track of their divisions and that the age-related HSC functional changes including the loss of capacity for self-renewal and long-term repopula-tion occur primarily after the HSC divides five times. It should be noted, however, that the recent work by Morcos et al [108] questioned the validity of conclusions by Bernitz et al, demonstrating considerable accumulation of background fluorescence in aged HSCs due to leaky fluorescent H2B histone expression, which was misinterpreted as stable retention of label. A part of the supposed timing mechanism may be represented by telomeres that progressively shorten with age in human HSCs isolated from fetal liver, umbilical cord blood, or adult bone marrow in parallel with greatly reduced proliferative potential [109].…”
Section: Hematopoietic Cells During Agingmentioning
confidence: 92%
“…B6.RFP mice with ubiquitious tdRFP expression were generated by germline excision of the lox P flanked STOP cassette (LSL) in R26 LSL-tdRFP animals employing the pgk-Cre transgene 43 . Pulse-chase data of unperturbed R26 rtTA /Col1A1 H2B-GFP mice was previously published 27 . H2B-GFP mice were induced with doxycyclin (DOX) via chow (Ssniff Spezialdiäten, 625mg/kg for 10-11 wks or 2000 mg/kg for either 2-7 wks (this study) ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…3a). The in vivo values of differentiation rates, proliferation rates and population sizes can be measured by, respectively, HSC fate mapping 26 , dilution of fluorescently labeled histones (e.g., H2B-GFP 27 ), and cell counting. We reasoned that obtaining these data for all cell populations in a stem cell differentiation pathway will also yield the pathway topology.…”
Section: Combining Es Hsc Fate Mapping With Mitotic Tracking Yields Lmentioning
confidence: 99%